Environmentally Conscious Character Building through Scouting Activities: A Case Study at RA Diponegoro - Rohmah Putri Arista; Anggrainy Henny; Padilah Siti Nur; Susiati; Winarsih Sri (Universitas Islam Balitar, 2026)
As the issue of environmental degradation grows, significant questions about how early childhood education may effectively and sustainably support the formation of environmentally sensitive character emerge. Despite the widespread discussion of the importance of environmental education from a young age, PAUD's teaching methods are still primarily verbalistic and do not provide children with real-world experiences. With the existence of Prasiaga Scout activities, formal and non-formal education becomes easier in carrying out environment-based learning, because the environment can be accessed by children in a real and collaborative way. The research method we use is descriptive qualitative by considering the objectives of constructivist learning in this research. Data collection techniques in this study include observation, interviews, and documentation of Prasiaga Scout activities at RA Diponegoro, the data was reduced, presented, and conclusions were drawn. The results of the study show that via direct interaction with nature, Pramuka Prasiaga activities can raise environmental consciousness, cultivate compassionate attitudes, and develop tangible pro-environmental actions in young children. According to the study's findings, Pramuka Prasiaga is a useful and successful educational tool for helping young children form environmentally sensitive personalities.